En dæmpet Eksplosion: Bevidsthedsrepræsentation i Tom Kristensens Hærværk - Ishøy, Mette Elholm (Danske Studier, 2024)
As a result of comparative readings of Tom Kristensen’s Hærværk (1930) and James Joyce’s Ulysses (1922), the general perception in most current secondary literature is that Hærværk unfolds through the protagonist Ole Jastrau’s inner world and that Tom Kristensen’s way of presenting consciousness is far less pioneering than Joyce’s. With Dorrit Cohn’s modes of ‘psycho-narration’ and ‘narrated monologue’ which she introduces in Transparent Minds – Narrative Modes for Presenting Consciousness in Fiction (1978) as theoretical basis I seek to differentiate this view. Each mode/technique describes a different way of presenting consciousness in third person fiction, although they are closely related. Throughout the paper it becomes clear that it is true that most parts of Hærværk relate to Ole Jastrau’s mental life, but that this is only possible through the presence of an intermediary narrator who is capable of representing the protagonist’s inner life through these narrative techniques. Furthermore it will be shown that Hærværk’s stylistic features may be different from Ulysses’, but that they are not necessarily less sophisticated.